KAJIAN MATAN DAN SYARAH HADIS TENTANG WAJIB MANDI BAGI PEREMPUAN YANG MIMPI BASAH - ANA CAHAYANI FATIMAH (FiTUA: Jurnal Studi Islam, 2020)
This article examines the traditions and traditions of traditions through the narration of Ahmad Bin Hanbal, it is found that the quality of traditions in terms of quality and traditions is authentic. and In the proposition of men and women who dreamed wet and then issued a semen, then he must take a shower. Conversely, if you do not issue semen, then you are not obliged to take a shower, because the reference for the bath is the discharge of the semen, not the dream. And if understanding and practicing the argument about compulsory bathing for women who have a wet dream will get a reward because Mandi Junub according to Shari'a is an obligation as the Word of the Prophet Muhammad, narrated by Abu Malik Al Asy'ari. The Messenger of God, may God bless him and grant him peace, said: Purification is part of faith (Narrated by Muslim) "Sanctity (cleanliness) is part of faith. while carrying out religious orders correctly according to the rules of Allah swt. which is contained in the Al-Qur'an and As-sunnah is given reward reward.